Influence of soil properties on archaeal diversity and distribution in the McMurdo Dry Valleys, Antarctica. Issue 2 (16th April 2014) - Richter, Ingrid; Herbold, Craig W.; Lee, Charles K.; McDonald, Ian R.; Barrett, John E.; Cary, Stephen C.
Abstract Archaea are the least understood members of the microbial community in Antarctic mineral soils. Although their occurrence in Antarctic coastal soils has been previously documented, little is known about their distribution in soils across the McMurdo Dry Valleys, Victoria Land. In this study, terminal‐restriction fragment length polymorphism (t‐RFLP) analysis and 454 pyrosequencing were coupled with a detailed analysis of soil physicochemical properties to characterize archaeal diversity and identify environmental factors that might shape and maintain archaeal communities in soils of the three southern most McMurdo Dry Valleys (Garwood, Marshall, and Miers Valley). Archaea were successfully detected in all inland and coastal mineral soils tested, revealing a low overall richness (mean of six operational taxonomic units [OTUs] per sample site). However, OTU richness was higher in some soils and this higher richness was positively correlated with soil water content, indicating water as a main driver of archaeal community richness. In total, 18 archaeal OTUs were detected, predominately Thaumarchaeota affiliated with Marine Group 1.1b (> 80% of all archaeal sequences recovered). Less abundant OTUs (2% of all archaeal sequences) were loosely related to members of the phylum Euryarchaeota. This is the first comprehensive study showing a widespread presence and distribution of Archaea in inland Antarctic soils.